Multiple verrucous squamous cell carcinomas developing on chronic hidradenitis suppurativa lesions—a rare case report from Romania - Fekete, Gyula László; Fekete, László; Iantovics, László Barna; Fekete, Júlia E.; Brihan, Ilarie (Frontiers in Medicine, 2024)
Hidradenitis suppurativa (HS) is an uncommon, recurrent, inflammatory skin illness of the apocrine glands, with a questionable etiology. The disease is associated with a multitude of comorbidities, of which the appearance of malignancy is the most important. Squamous cell carcinoma is considered the most frequent malignancy that can appear in HS. A case report of a 72-year-old male is presented, who suffered over 40 years from persistent, extensive hidradenitis suppurativa in stage Hurley III, on the buttocks and perianal region, who recently presented two verrucous semi-consistent, skin-colored tumors on the right buttock. The biopsy and histopathological exam confirmed a verrucous type of squamous cell carcinoma. There are about 100 reported clinical cases of squamous cell carcinoma complicating hidradenitis suppurativa in the literature, but only a few describe a verrucous carcinoma as a clinical form. The particularity of the case is the rare appearance of multiple verrucous types of squamous cell carcinomas in a male patient, in Hurley Stage III, with a long HS disease duration, appearing on the perianal/gluteal region, being the first case report in our country. We suggest that a tumor screening should be done for all the patients with HS who have these risks.